2018
DOI: 10.1007/978-3-319-77932-4_10
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Flow, Pulse Pressure and Pulse Wave Velocity in Men and Women at Various Ages

Abstract: The increase in pulse pressure (PP) that occurs with advancing age is predominantly due to reduced arterial distensibility leading to decreased aortic compliance, particularly in the elderly, in whom high blood pressure mainly manifests as isolated systolic hypertension. Since age-related changes in stroke volume are minimal compared with changes in PP, PP is often considered a surrogate measure of arterial stiffness. However, since PP is determined by both cardiac and arterial function, a more precise and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 27 publications
4
54
0
1
Order By: Relevance
“…Age-related arterial dysfunction is the result of a variety of deleterious changes that include intimal remodeling [9], increased arterial stiffness [10,11], and endothelial dysfunction [12,13]. Age-related changes in the physical properties of, and the interaction between, macro and a1111111111 a1111111111 a1111111111 a1111111111 a1111111111 microvasculature contribute to the development of WMHs [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Age-related arterial dysfunction is the result of a variety of deleterious changes that include intimal remodeling [9], increased arterial stiffness [10,11], and endothelial dysfunction [12,13]. Age-related changes in the physical properties of, and the interaction between, macro and a1111111111 a1111111111 a1111111111 a1111111111 a1111111111 microvasculature contribute to the development of WMHs [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that there were gender and age differences in PP. 30 Our study found that there was an inverse association between PP and age in young adults who did not take antihypertensive drugs. In addition, data from 71 629 untreated normotensive individuals demonstrated that PP has distinct characteristics affecting all-cause mortality, and PP may integrate the effects of age and gender on all-cause mortality.…”
Section: Discussionmentioning
confidence: 43%
“…The carotid-femoral pulse transit time (cfPTT) is 125 milli-seconds for this cardiac cycle, and for a straight-line distance of 70 centimeters between both the regions, this result in an effective PWV of 5.6 meters per second. The PWV estimates derived using the Doppler radar measurements fall within the normal range for healthy adults [11].…”
Section: Uponmentioning
confidence: 59%